KNOWLEDGE AND AWARENESS LEVEL OF THE GENERAL POPULATION OF SAUDIARABIA REGARDING HELICOBACTER PYLORI INDUCED GASTRIC ULCERS ANDCANCER: A CROSS- SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2024)
Background: Helicobacter pylori (H. pylori) is a bacterium that infects the stomach. It is the mostbacterial infection in the world. H. pylori infection can cause a variety of gastric diseasescommon,including gastritis, gastric ulcer, and gastric cancer. . The purpose of this study was to assess Knowledgeand Awareness level of Saudi population regarding Helicobacter Pylori induced gastric ulcer andcancer.Methods: A cross-sectional study involving 28 item questionnaire-based assessment was carried outby enrolling and taking prior consent for Saudi people of either sex aged above 18 years. The studyinstrument was divided into three modules allocating questions and analyzed.Results: As regard knowledge and awareness score about H.Pylori, a majority of the respondents(51.6%) possess a low level of knowledge about this common gastric pathogen. (37.8%) exhibits amoderate level of understanding and a relatively small percentage (10.6%) with a high level ofknowledge and awareness. Regarding the attitude score about H.Pylori, 47.4%, exhibited a neutralattitude. Conversely, a significant proportion, 33.2%, demonstrated a positive attitude and 19.4% of therespondents exhibited a negative attitude.Conclusion: the study revealed a concerning lack of knowledge and awareness among the generalpopulation regarding Helicobacter pylori-induced gastric ulcers and cancer. The majority of respondentsexhibited a low level of knowledge about this common gastric pathogen, highlighting the need foreducational initiatives and public awareness campaigns.